Muscle lesion treatment in Brazilian soccer players: Theory vs. Practice - Almeida, Fernando de Souza; Mainine, Sergio; de Abreu, Luiz Carlos; Valenti, Vitor E.; Ferreira, Celso; Fonseca, Fernando L. A.; Macedo Junior, Hugo; de Carvalho, Tatiana Dias; Valenti, Erica E.; Moreno, Isadora L.; Goncalves, Ana Clara C. R. [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP]; et al. (Drunpp-sarajevo, 2012)
Background: In this study we evaluated the rehabilitation profile of Brazilian soccer players which underwent lower limb muscle lesions.Methods: This is a descriptive investigation. We evaluated 139 professional soccer players (1724 years old). We evaluated the following variables: muscle lesion diagnosis, symptoms, non steroidal anti-inflammatory used, physiotherapy treatment, which physiotherapy recourses was used if treated and train adaptation.Results: In great part of the athletes muscle lesion remained between 2 weeks and 1 month. Around 54% were diagnosed by a physician; the other part was diagnosed by a physical therapist. Non steroidal anti-inflammatory were prescribed by physicians in 42% of the cases; in 7% the physical therapist prescribed the medication while in 49% of the cases the masseur prescribed the drug. More than 1/4 of the athletes received physiotherapy treatement between 48 hours and 5 days. Isometric exercise therapy was applied in 15% of the cases. 63% were not accompanied by the physiotherapist on their return to the field. 48% received massages immediately after injury.Conclusion: We presented discrepancy between the recommended theory described by several researches and the practice. We indicate the necessity of recycling in a general context the rehabilitation of muscle injuries.
Keywords: Sport; Sport Medicine; Athletic Therapy; Clinical Evaluation; Clinical Research; Injury Management